Effect of E. coli biofilm formation and removal on passive films on AISI 316L during fermentation processes. (June 2021) - Di Franco, F.; Tranchida, G.; Pupillo, D.; Ghersi, G.; Cinà, P.; Virtanen, S.; Santamaria, M.
Graphical abstract: Highlights: SS coupons were immersed in a pilot fed-batch fermenter in presence of E- Coli . Biofilm formation on AISI 316 L after sanitization with hot water vapour was studied. During sanitization an iron enrichment in passive films occurs. EIS spectra suggest Cr enrichment in the passive film during fermentation. A disinfection of 30 min at 25 °C in NaClO was effective for biofilm removal. Abstract: 316L coupons were sanitized in hot water vapour inducing iron enrichment in passive films. Coupons were then immersed in a pilot fed-batch fermenter in presence of E. coli . Sanitization causes iron enrichment in passive films. Fermentation causes the growth of biofilm on the SS, constituted by bacteria embedded in an extracellular polymeric substance. During fermentation SS open circuit potential is very negative due to low oxygen concentration on its surface, while the chelating action of siderophores induces chromium enrichment in the passive film. Disinfection in NaClO for 30 min allows removal of biofilm and formation of a protective passive film.